Aggression and violence against medico-legal healthcare personnel of the Italian National Institute of Social Security (INPS): Analysis of the phenomenon and management strategies - Gaetana STELITANO; Amelia RIZZO; Diego BURZOMATI (GIornale Italiano di Psicologia e Medicina del Lavoro, 2025)
The issue of aggression and violence against medico-legal healthcare personnel, such as that of the Italian National Institute of Social Security (INPS), is a growing concern. This phenomenon, encompassing both verbal and physical behaviors, severely impacts the well-being of staff and the quality of service. An analysis of this issue highlights various triggering factors, including patient dissatisfaction with medical evaluations, perceptions of injustice, and frustration with complex bureaucratic processes. These factors can significantly increase the risk of aggressive behavior, necessitating the implementation of effective preventive strategies. De-escalation has proven to be effective in these contexts, as it aims to reduce aggression before it escalates into open violence. Techniques employed include clear and empathetic communication, emotional self-regulation by staff, and timely recognition of early signs of aggression. Additionally, environmental management and physical safety measures play an important role in preventing situations from worsening. The application of de-escalation techniques emerges as a key strategy for managing such incidents, reducing the risk of escalation and improving the safety of both staff and patients. Nevertheless, further research is needed to develop specific guidelines for the training of medico-legal personnel, tailoring de-escalation techniques to the unique challenges of their work environment, where emotional pressure and stress are particularly high.